Rwanda : Can Parenting Programs Improve Child Development and Prevent Violence Against Women and Children? - World Bank (World Bank, Washington, DC, 2021)
Children need a safe, nurturing, healthy, and stimulating environment to thrive and reach their full potential. But millions of children living in poverty don’t receive enough stimulation or good nutrition in their first years of life, and poverty also makes them more likely to experience neglect and violence in the home. Domestic violence, however, is rarely addressed in programs promoting young children’s development, which also typically focus on mothers, with little attention on fathers. Previous research suggests home-based parenting programs can lead to positive improvements in children’s brain development. Can these programs be adapted to address family violence as well Can these services be effectively delivered through government social safety net programs which often target poor, vulnerable families